855. IRIS STOLONIFERA: Iridaceae. (April 2017) - Rix, Martyn; Strange, Kit
Summary: Iris stolonifera Maxim., from central Asia is illustrated. Its history is examined and current cultivars are listed. Suggestions for its cultivation are given.